CONTRIBUTION OF ALIBABA B2B MODEL TO SME - Zhang Wei; Arty Pandey (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The business model describes the basic principles of how an enterprise creates value, transmits value, and obtains value. It is the logic of business activities. The choice of a business model that suits the company can enable the company to be in an advantageous position in market competition. B2B business model helps companies. The scope of activities has been expanded, making it easier for companies to develop across regions and borders at lower costs. With the acceleration of the Internet + economic development process, our country's rapidly rising e-commerce has begun to become a brand-new way of foreign trade. And B2B has a significant advantage in e-commerce. B2B is also expected to become a new growth point in our country's Internet trade. In the context of the rapid development of the B2B model, more small and medium-sized enterprises have obtained development opportunities and found new development models. The Internet provides an online platform for small and medium-sized enterprises to conduct direct transactions with merchants, saving communication costs and road losses. In addition, SMEs' development models and development space have also changed. This article will further study the contribution of Alibaba's B2B model to SMEs enterprise, confirming the impact of the B2B model on all aspects of enterprise development through data.